Bioactive Molecules from the Alpinia Genus: A Comprehensive Review - Dash, Santwona; Panda, Manasa K.; Singh, Mayanglambam C.; Jit, Bimal P.; Singh, Yengkhom D.; Patra, Jayanta K. (Current Pharmaceutical Biotechnology, 2020)
Background: Floral has diversity and unique nature due to the complex structure and component. Alpinia is an important genus of the Zingiberaceae family having complex taxonomical diversity. The presence of many unique bioactive molecules makes this genus, a pharmaceutically important genus. They provide a wide range of medicinal properties, including traditional remedies to modern therapeutic applications. Methods: Extracts of Alpinia mostly contain bioactive molecules and secondary metabolites such as polyphenolics, tannins, flavonoids and other therapeutically important compounds. These bioactive molecules are biologically active, treating against inflammation, cancer, arterial hypertension, and other deadly diseases. Results: These bioactive molecules can act as natural enzyme inhibitors for some of the deadly diseases and can block the pathway for metabolic activities. In addition, these genera have played a major role in multidisciplinary studies of phytochemistry, ethnobotany, and pharmacological aspects in day-to-day life. Conclusion: Therefore, this review highlights the fewer known facts of the genus Alpinia in terms of bioactive molecules and its significant therapeutic applications to help in combating major diseases of humans.
Keywords: neurological diseases